Experience with partial nephrectomy for renal cell carcinoma - Tanaka, T (Hinyokika kiyo. Acta urologica Japonica, 2001)
From Sept. 1991 to Jan. 1999, we performed partial nephrectomy on 7 patients with renal cell carcinoma. The indication was imperative for 3 patients, and elective for 4 patients. The 3 imperative cases consisted of bilateral renal cell carcinomas, a polycystic kidney disease and a contralateral atrophic kidney. All 4 patients with elective indication revealed renal cell carcinoma with a normal functioning contralateral kidney. The tumor size ranged from 1.3 cm to 6.0 cm (2.7 cm on average). The mean clamping time of renal artery was 22 minutes and mean blood loss was 400 ml. The pathological stage was pT1a in 6 patients and pT1b in one patient. Postoperative follow-up ranged from 4 months to 92 months (mean: 43 months). One patient with bilateral renal cell carcinoma died of metastases to the lungs and brain at 25 months postoperatively. The remaining 6 patients are alive without recurrence and metastasis. We obtained a good postoperative course in our selected patients with low stage. Thus it was considered that partial nephrectomy is effective against small renal cell carcinoma